Perlindungan Hukum Terhadap Konsumen dalam Transaksi Akuntansi Bisnis Online - Nadia Sahira Aqila; Nailah Yustisia; Sri Handayani (Advokasi Hukum & Demokrasi (AHD), 2025)
This research aims to analyze legal protection for consumers in online business transactions. In the increasingly developing digital era, online business has become one of the main choices for consumers in carrying out buying and selling transactions. However, this rapid growth also presents various risks and challenges for consumers. This research uses a normative analysis method by referring to applicable legal regulations and relevant literature studies. The research results show that legal protection for consumers in online business transactions has been regulated in several laws and regulations that apply in many countries. One important aspect of this legal protection is the provisions regarding information that must be conveyed by sellers to consumers, including information about products, prices and delivery conditions. Apart from that, there are also provisions regarding consumers' rights to file complaints and receive compensation if their rights are violated. In this regard, effective dispute resolution mechanisms and easy access to the justice system must be available to consumers.